CMOS BASED THERMAL ENERGY GENERATOR - ABDUL RAHMAN, ZATI HANANI (2014)
Energy harvesting techniques have been used as a secondary power source in various battery-operated applications to extend the operating time of the targeted device supplementing to the limited power provided by the battery. Among numerous techniques available, thermal energy harvesting has been the most widely practiced in converting heat into electrical energy, as heat can be found in natural and also manmade environments. Electrical energy is harvested from heat by means of thermal energy generator (TEG) using Seebeck effect mechanism. The purpose of this study is to propose a new concept of TEG with sufficient capability to detect temperature differences between two junctions with standard CMOS microfabrication technology compatibility. It consists of p-type and /?-type polysilicon thermocouples arranged thermally in parallel and electrically in series.